Studying of quality parameters of Hungarian and Greek honey samples - Széles, Éva; Borbély, Mária; Prokisch, József; Kovács, Béla; Vlachos, Ilias; Alissandrakis, Eleftherios K.; Harizanis, Paschalis C.; Győri, Zoltán (Acta Agraria Debreceniensis, 2007)
Honey has been a valuable food for mankind since ancient times. It was the only sweetener until the start of industrial sugar mass production. Honey plays an important role in our nutrition and its positive effects on health are well-known. The quality of Hungarian honey is perfect, so it is very important to safeguard and monitor its quality continuously and to build up a good traceability and quality assurance system. For such a system, it is necessary to study the nutritional properties and the origin of different honey samples. In our study, we study Hungarian and Greek honey.